R. A. Maryks, The Jesuit Order as a Synagogue of Jews. Jesuits of Jewish Ancestry and Purity-of-Blood Laws in the Early Society of Jesus - Prades Vilar, Mario (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2011)
Nota crítica de R. A. Maryks, The Jesuit Order as a Synagogue of Jews. Jesuits of Jewish Ancestry and Purity-of-Blood Laws in the Early Society of Jesus